Recombinant Full-Length Hepatitis C Virus E1E2 Dimer Elicits Pangenotypic Neutralizing Antibodies - Lin, Tianli; Chi, Xiaojing; Liu, Xiuying; Pan, Shengnan; Chen, Wenfang; Duan, Huarui; Zhang, Xinhui; Yang, Wei (Frontiers in Immunology, 2022)
An effective prophylactic vaccine would be beneficial for controlling and eradicating hepatitis C virus (HCV) infections. However, the high diversity across HCV genotypes is a major challenge for vaccine development. Selection of the appropriate immunogen is critical to elicit broad HCV neutralizing antibodies (NAbs). To increase the antigenic coverage of heterodimer glycoproteins, we designed and produced recombinant E1E2 antigens for genotypes 1a/1b/2a/3a/6a from an IgG Fc-tagged precursor protein in FreeStyle 293-F cells. The recombinant E1 and E2 antigens were localized and associated with the endoplasmic reticulum and co-purified from membrane extracts. By examining the interactions with HCV entry co-receptors and the blockade of HCV infection, we found that these purified Fc-E1E2 proteins displayed correct folding and function. Mouse immunization results showed that each recombinant E1E2 antigen could elicit a pangenotypic antibody response to itself and other genotypes. We also found that the pentavalent formula triggered a relatively higher and more uniform NAb titer and T cell response than monovalent antigens. Taken together, our findings may provide a useful strategy for the vaccine development of HCV and other viruses with highly heterogeneous surface glycoproteins.